PERBANDINGAN GAYA KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL DALAM UPAYA MENINGKATKAN KINERJA ORGANISASI (STUDI PADA LOKA POM DI KABUPATEN KEPULAUAN SANGIHE DENGAN LOKA POM DI KABUPATEN BANGGAI) - Ermanto Siahaan; S. L. H. V. Joyce Lapian; Agus Supandi Soegoto (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
ABSTRACT: This study aims to determine the differences between transactional and transformational leadership styles. Through a comparative quantitative approach, this study compares the effectiveness of the two leadership styles in improving organizational performance in two different locations, namely the POM Center in Sangihe Islands Regency and the POM Center in Banggai Regency. To test the existing differences, the data were analyzed using the independent sample t-test statistical technique. The results of the study indicate that (1) there is a significant difference in transactional leadership styles in the POM Center in Sangihe Islands Regency and Banggai Regency in efforts to improve organizational performance. The transactional leadership style is better than the transactional leadership style in the POM Center in Banggai Regency (2) There is no significant difference in transformational leadership styles in the POM Center in Sangihe Islands Regency and Banggai Regency in efforts to improve organizational performance. The transformational leadership style is better than the transformational leadership style in the POM Center in Banggai Regency